Guest Editor's Introduction: Supporting Urgent Basic Reading Skills in Children in Africa and Around the World - Lyytinen, Heikki; Richardson, Ulla (Human Technology, 2014)
Even in the 21st century, the need of support in literacy acquisition around the world remains huge. Data presented in a UNESCO-commissioned report (Education for All, 2014) estimates that 250 million children worldwide need reading support, with the largest number of countries in need located in Sub-Saharan Africa. Having poor reading skills is a huge problem for the individuals themselves as well as their societies. In today’s information societies, the majority of learning materials are mediated via written text. Thus, literacy is vital for individuals’ quality of life, their educations, career choices, and thus to the world economy and the development of democracy.